2006
DOI: 10.1152/ajpheart.01148.2005
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral renin-angiotensin systems in ouabain-induced hypertension

Abstract: Chronic subcutaneous infusion of ouabain causes hypertension via central pathways involving angiotensin type 1 (AT(1)) receptor stimulation. The present study assessed plasma and tissue ANG I and II levels as well as AT1 receptor and angiotensin-converting enzyme (ACE) mRNA levels and binding densities by real-time PCR and in vitro autoradiography in relevant brain nuclei and peripheral tissues (heart and kidney) in rats at 1 and/or 2 wk after start of ouabain infusion at 50 microg/day. After 2 wk (but not aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 29 publications
1
9
0
4
Order By: Relevance
“…Similar magnitude of hypertensive effects by cardiac glycosides was observed with ouabain infused for 2 weeks (118Ϯ2 versus 103Ϯ2 mm Hg; PϽ0.05). 32 We further confirmed that the given MBT was excreted into urine. This means that MBT acts as a vasopressor substance in rats without any toxic effects on kidney function, because serum creatinine and urea nitrogen levels were not influenced by MBT.…”
Section: Discussionsupporting
confidence: 71%
“…Similar magnitude of hypertensive effects by cardiac glycosides was observed with ouabain infused for 2 weeks (118Ϯ2 versus 103Ϯ2 mm Hg; PϽ0.05). 32 We further confirmed that the given MBT was excreted into urine. This means that MBT acts as a vasopressor substance in rats without any toxic effects on kidney function, because serum creatinine and urea nitrogen levels were not influenced by MBT.…”
Section: Discussionsupporting
confidence: 71%
“…The release of angiotensin II may act on vascular smooth muscle, promoting vasoconstriction and increasing peripheral resistance and, consequently, the diastolic pressure (32). Considering that ouabain stimulates angiotensin II release (15,17) and increases sympathoexcitatory activity (14), the sharp reduction of the pressor reactivity to phenylephrine after blockade of the renin-angiotensin system could be explained by a reduced stimulation of the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism(s) by which acute administration of nanomolar concentrations of ouabain, similar to the normal plasma concentrations (2), exerts its effects in vivo on blood pressure and on pressor responses to vasoconstrictor agents is still under debate. It is not clear yet which is the contribution of central (15,16) or peripheral mechanisms (9,12,17), or of both simultaneously to this increased pressor response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forms of hypertension that are mediated by increases in brain concentration of OLS or ouabain are abolished by ICV losartan [e.g., a high-salt diet in Dahl-S rats (62); Wistar rats and mice given ICV sodium-rich aCSF (20,51); rats and mice given ICV ouabain (7,51)]. Thus, chronic inhibition/downregulation of the brain Na ϩ -K ϩ -ATPase by the brain OLS or by ICV ouabain increases blood pressure by activating the brain RAS.…”
Section: Brain Ras Functionmentioning
confidence: 99%